PERAN GURU DALAM MENGEMBANGKAN KURIKULUM MERDEKA DI SD NEGERI 060855 - Cut Farida Zuhra; Lutfia Permatasari; Muhammad Torkis Lubis; Rahmadani Dalimunte; Sri Rizki Wardani Simanjuntak (Kampus Akademik Publiser, 2024)
This research investigates the role of teachers in developing an independent curriculum in elementary schools (SD). Through a qualitative approach, data was collected through interviews and observations of elementary school teachers involved in curriculum development. The research results show that teachers have a crucial role in the process of developing an independent curriculum, including identifying student needs, adapting the curriculum to the local context, using available resources effectively, as well as evaluating and improving regularly. The implication of this research is the need for ongoing support for teachers in developing an independent curriculum to ensure its relevance, sustainability and success in improving learning in elementary schools (SD).